Silicone pressure-sensitive adhesive composition having polysiloxane containing methyl phenyl group, silicone pressure-sensitive adhesive film, method of manufacturing the same
The silicone adhesive composition with a dual network structure addresses the challenges of adhesion and durability in extreme environments by providing excellent low-temperature adhesiveness and elastic recovery, suitable for flexible displays and wearable devices.
Patent Information
- Application Number
- KR1020260085632
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-05-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-05-12
AI Technical Summary
Existing silicone adhesives fail to provide excellent adhesion, initial tack, and high-reliability peel strength under extreme environments and repeated deformation, which are critical for flexible displays, high-flexibility batteries, and wearable devices.
A silicone adhesive composition with a dual network structure formed by crosslinking a methylphenyl group-containing polysiloxane and a polysiloxane adhesive resin, comprising a first crosslinker with a partially crosslinked random structure and a second crosslinker with a continuous three-dimensional network, creating an interpenetrating dual network.
The composition achieves excellent low-temperature adhesiveness, elastic recovery, and durability, maintaining stability in extreme environments.
Smart Images

Figure 112026057428929-PAT00016_ABST
Abstract
Description
Technology Field
[0001] The technical concept of the present invention relates to a silicone adhesive composition containing a methylphenyl group-containing polysiloxane, a silicone adhesive film, and a method for manufacturing the same. Background Technology
[0002] Silicone adhesives are used in various industrial fields based on their excellent heat resistance, chemical resistance, and structural stability. In particular, they offer the advantage of providing stable adhesive performance over a wider temperature range compared to acrylic adhesives. This is attributed to the inorganic framework structure and high free volume of silicone polymers. However, to meet the requirements for extreme environments and durability under variable stress demanded by flexible displays, high-flexibility batteries, and wearable devices, simply ensuring low temperature performance is no longer sufficient. Excellent adhesion to the substrate, initial tack, and high-reliability peel strength are emerging as important performance factors. The problem to be solved
[0003] The technical problem that the technical concept of the present invention aims to solve is to provide a silicone adhesive composition containing a methylphenyl group-containing polysiloxane, a silicone adhesive film, and a method for manufacturing the same.
[0004] However, these tasks are exemplary, and the technical concept of the present invention is not limited thereto. means of solving the problem
[0005] According to one aspect of the present invention, a silicone adhesive composition comprising a methylphenyl group-containing polysiloxane, a silicone adhesive film, and a method for manufacturing the same are provided.
[0006] According to one embodiment of the present invention, the silicone adhesive composition comprises: a first crosslinker comprising a first crosslinked network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinker comprising a second crosslinked network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, wherein the first crosslinked network and the second crosslinked network may form an interpenetrating dual network structure.
[0007] According to one embodiment of the present invention, the methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0008] According to one embodiment of the present invention, the methylphenyl group-containing polysiloxane may have the following chemical formula.
[0009]
[0010] (Here, n is between 15 and 300 inclusive, and m is between 2 and 256 inclusive)
[0011] According to one embodiment of the present invention, in the methylphenyl group-containing polysiloxane, the fraction of methylphenyl groups may be in the range of 0.5 mol% to 5 mol%.
[0012] According to one embodiment of the present invention, the methylphenyl group-containing polysiloxane may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol.
[0013] According to one embodiment of the present invention, the silicone adhesive composition is -20 o It can have a glass transition temperature of C or less, an elastic recovery rate of 80% or more, and a peel strength of 8 N / 25 mm or more.
[0014] According to one embodiment of the present invention, the first crosslinker comprises 0.05 to 0.2 parts by weight of a monomeric first siloxane-based crosslinker per 10 parts by weight of the methylphenyl group-containing polysiloxane, and the second crosslinker may comprise 1 to 5 parts by weight of the first crosslinker and 0.5 to 2 parts by weight of a polyfunctional second siloxane-based crosslinker per 100 parts by weight of the polysiloxane adhesive resin.
[0015] According to one embodiment of the present invention, the first crosslinker may have a molar ratio (Si-H / vinyl mol ratio) of the Si-H group of the siloxane-based crosslinker and the vinyl group of the methylphenyl group-containing polysiloxane in the range of 0.3 to 1.2, and may have a gel fraction in the range of 15% to 65%.
[0016] According to one embodiment of the present invention, the polysiloxane adhesive resin may comprise at least one of polydimethylsiloxane (PDMS), dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer.
[0017] According to one embodiment of the present invention, the polysiloxane adhesive resin may further include a resin composed of a network-type oligomer and having a vinyl group or a hydride group at the end.
[0018] According to one embodiment of the present invention, the silicone adhesive composition may further comprise: a first siloxane-based crosslinking agent comprising at least one of branch-type hydrosiloxane, multi-hydride siloxane, and silsesquioxane-based hydrosiloxane; and a second siloxane-based crosslinking agent comprising at least one of polyorganohydrosiloxane, methylhydrosiloxane-dimethylsiloxane copolymer, hydride-terminated siloxane, and hydride-functional silicone resin.
[0019] According to one embodiment of the present invention, the silicone adhesive film comprises a film substrate; and a silicone adhesive composition applied and cured on the film substrate, wherein the silicone adhesive composition comprises a first crosslinking material comprising a first crosslinking network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinking material comprising a second crosslinking network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, and the first crosslinking network and the second crosslinking network may form an interpenetrating dual network structure.
[0020] According to one embodiment of the present invention, the methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0021] According to one embodiment of the present invention, the silicone adhesive composition is -20o It can have a glass transition temperature of C or less, an elastic recovery rate of 80% or more, and a peel strength of 8 N / 25 mm or more.
[0022] According to one embodiment of the present invention, a method for manufacturing the silicone adhesive film may comprise: a step of providing a polysiloxane containing a methylphenyl group; a step of adding the polysiloxane containing a methylphenyl group, a monomolecular first siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a first crosslinking target; a step of crosslinking the first crosslinking target to form a first crosslinked material comprising a first crosslinking network having a partially crosslinked random structure formed by crosslinking the polysiloxane containing a methylphenyl group; a step of adding the first crosslinked material, a polysiloxane adhesive resin, a multifunctional second siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a second crosslinking target; a step of applying the second crosslinking target onto a film substrate; and a step of crosslinking the second crosslinking target to form a second crosslinked material comprising a second crosslinking network formed by crosslinking the polysiloxane adhesive resin.
[0023] According to one embodiment of the present invention, the first bridge network and the second bridge network can form an interpenetrating dual network structure.
[0024] According to one embodiment of the present invention, the first crosslinking target may comprise, with respect to 100 parts by weight of an organic solvent, 5 to 20 parts by weight of the methylphenyl group-containing polysiloxane, 0.05 to 0.2 parts by weight of a first siloxane-based crosslinking agent, and 0.005 to 0.1 parts by weight of a platinum catalyst, and the second crosslinking target may comprise, with respect to 100 parts by weight of an organic solvent, 1 to 5 parts by weight of the first crosslinking agent, 95 to 99 parts by weight of a polysiloxane adhesive resin, 0.5 to 2 parts by weight of a second siloxane-based crosslinking agent, and 0.1 to 2 parts by weight of a platinum catalyst.
[0025] According to one embodiment of the present invention, the step of forming the first crosslinking material comprises 80 of the first crosslinking target material o C to 120 o The step of forming the second crosslinker, which is carried out by a crosslinking reaction at a temperature in the C range, comprises 120 of the second crosslinker target. o C to 140 o It can be achieved through a cross-linking reaction at a temperature in the C range.
[0026] According to one embodiment of the present invention, the step of providing the methylphenyl group-containing polysiloxane may include: a step of forming a first mixture by stirring a siloxane oligomer and a retardant; a step of forming a second mixture by stirring the first mixture and the methylphenyl siloxane; a step of forming a third mixture by stirring the second mixture and a platinum catalyst; and a step of polymerizing the siloxane oligomer and the methylphenyl siloxane by heating the third mixture.
[0027] According to one embodiment of the present invention, after performing the polymerization step, methylphenylsiloxane can be added to the polymerized polysiloxane formed to form a polysiloxane having a desired molecular weight, and the polymerization reaction can be repeated. Effects of the invention
[0028] According to the technical concept of the present invention, methylphenyl group-containing polysiloxanes can effectively control the crystallization behavior of siloxane chains while using a relatively low content of phenyl groups, thereby simultaneously improving low-temperature properties, flexibility, and structural stability. In addition, by controlling the arrangement structure of the phenyl groups, the physical properties of the siloxane chains can be precisely controlled, thereby improving the freedom of material design and allowing the material to be utilized as a high-performance silicone material capable of maintaining stable properties even in extreme environments.
[0029] In addition, the silicone adhesive composition according to the present invention can realize an interpenetrating double network structure by forming a first cross-linking network using a methylphenyl group-containing polysiloxane comprising methylphenylsiloxane units of an AnB-type structure in which phenyl groups are periodically arranged, and then mutually bonding with a second cross-linking network formed by a polysiloxane adhesive resin. The interpenetrating double network structure may be referred to as an interpenetrating double cross-linking structure.
[0030] In particular, the first crosslinking network may have a partially crosslinked random structure formed by a monomolecular first siloxane-based crosslinking agent, and can provide uniformly dispersed crosslinking points while maintaining the mobility of the siloxane chains. Furthermore, since the first crosslinking network can alleviate stress concentration and suppress network collapse through a localized crosslinking structure, it can provide excellent flexibility and elastic recovery characteristics even in environments of repeated deformation and low temperature.
[0031] In addition, the second crosslinking network may have a continuous three-dimensional network structure formed by a multifunctional second siloxane-based crosslinking agent, and can improve the cohesiveness, structural stability, and adhesive reliability of the adhesive layer. Accordingly, the first crosslinking network and the second crosslinking network act complementarily to simultaneously achieve excellent low-temperature adhesive properties, elastic recovery, and durability.
[0032] Accordingly, the silicone adhesive composition according to the present invention and the silicone adhesive film containing the same may have excellent low-temperature adhesiveness, elastic recovery, cohesiveness, and durability, and can be effectively applied in fields exposed to repeated deformation and extreme environments, such as flexible displays, foldable electronic devices, high-flexibility batteries, and wearable electronic devices.
[0033] The effects of the present invention described above are illustrative and the scope of the present invention is not limited by these effects. Brief explanation of the drawing
[0034] FIG. 1 illustrates a method for manufacturing a methylphenyl group-containing polysiloxane included in a silicone adhesive composition according to one embodiment of the present invention using a chemical formula. FIG. 2 is a flowchart illustrating a method for manufacturing a methylphenyl group-containing polysiloxane included in a silicone adhesive composition according to an embodiment of the present invention. FIG. 3 is a flowchart illustrating a method for manufacturing a silicone adhesive film comprising a methylphenyl group-containing polysiloxane according to an embodiment of the present invention. FIG. 4 illustrates a conceptual diagram of the formation of a double network structure of a silicone adhesive film according to an embodiment of the present invention. Specific details for implementing the invention
[0035] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the attached drawings. The embodiments of the present invention are provided to more completely explain the technical concept of the present invention to those skilled in the art, and the following embodiments may be modified in various different forms, and the scope of the technical concept of the present invention is not limited to the following embodiments. Rather, these embodiments are provided to make the present disclosure more faithful and complete and to fully convey the technical concept of the present invention to those skilled in the art. In this specification, the same reference numerals denote the same elements throughout. Furthermore, various elements and areas in the drawings are depicted schematically. Accordingly, the technical concept of the present invention is not limited by the relative sizes or spacing depicted in the attached drawings.
[0036] The technical concept of the present invention is to provide a silicone adhesive composition comprising a methylphenyl group-containing polysiloxane having excellent adhesive strength that can be applied to flexible displays, high-flexibility batteries, wearable devices, etc.
[0037] It should be noted that in this specification, "polymerization" may be interpreted to mean copolymerization.
[0038] In the following, methylphenyl group-containing polysiloxanes will be described in detail.
[0039] methylphenyl group-containing polysiloxane
[0040] Polysiloxanes containing methylphenyl groups can effectively suppress chain crystallization at low temperatures with only a minimal introduction of phenyl groups by precisely controlling the position and periodicity of the phenyl groups present within the polysiloxane chain.
[0041] The above methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0042] The above repetition unit may be repeated m times (where m is between 2 and 256).
[0043] The above methylphenyl group-containing polysiloxane may have a structure in which the above An is disposed at each of both ends.
[0044] The above methylphenyl group-containing polysiloxane may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol. If the molecular weight is less than 10,000 g / mol, the flowability is low, making it difficult to commercialize. If the molecular weight exceeds 1,000,000 g / mol, there are difficulties in the formulation and processing of polymer materials. For example, if the molecular weight is 100,000 g / mol, it can provide the advantages of excellent flowability and processability in commercialization of products such as sealants, adhesives, and rubber.
[0045] The above methylphenyl group-containing polysiloxane may have the following chemical formula. Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less.
[0046]
[0047] The above dimethylsiloxane may be composed of a siloxane oligomer having the following chemical formula.
[0048]
[0049] The above methylphenylsiloxane may have the following chemical formula.
[0050]
[0051] In the above methylphenyl group-containing polysiloxane, the portion where the dimethyl siloxane and the methylphenyl siloxane are bonded may have the following chemical formula. Here, the central carbon atoms may be bonded by a single bond.
[0052]
[0053] The above methylphenyl group-containing polysiloxane may have a terminal portion containing a vinyl group of the following chemical formula at at least one end. For example, the above methylphenyl group-containing polysiloxane may have the vinyl group at both ends.
[0054]
[0055] In the above methylphenyl group-containing polysiloxane, the periodicity of the phenyl group of the methylphenyl siloxane can be determined by the molecular weight of the siloxane oligomer. That is, if the siloxane oligomer is long, the phenyl group can be arranged to have long periodicity.
[0056] The molecular weight can be increased through step polymerization. For example, when An, B, and An are polymerized, it may have the structure AnBAn; when AnBAn, B, and AnBAn are polymerized, it may have the structure AnBAnBAnBAn; and when AnBAnBAnBAn, B, and AnBAnBAnBAn are polymerized, it may have the structure AnBAnBAnBAnBAnBAnBAnBAnBAnBAn. Here, it should be noted that An does not represent a single functional group of (CH3)2-Si-O, but refers to n dimethylsiloxane structures represented as [(CH3)2-Si-O]n, which may be an oligomer.
[0057] For example, when considering an ABAB alternating structure, if A is a single functional group of (CH3)2-Si-O, the cluster size of A differs from that of the present invention. In such an ABAB alternating structure, the flexibility characteristic of siloxane is lost, leading to brittleness, an increase in the glass transition temperature (Tg), and an increase in the refractive index, resulting in increased opacity, among other limitations.
[0058] The above methylphenyl group-containing polysiloxane has an alternating AnBAnB structure, wherein An comprises dimethylsiloxane having n clusters rather than a single functional group. Accordingly, the flexibility of the siloxane chain can be maintained, and the methylphenylsiloxane (B), which is periodically and sparsely arranged, can act as an inter-chain aggregation at high temperatures.
[0059] Here, n may be 15 or more and 300 or less, and preferably n may be 30 or more and 300 or less. If n is less than 15, brittleness may occur and the glass transition temperature (Tg) may increase. If n is greater than 300, the periodicity of the methylphenylsiloxane (B) being placed becomes too long, and the effect of the methylphenylsiloxane (B) becomes negligible.
[0060] The methylphenylsiloxane (B) may be in the range of 1 mol% to 5 mol% with respect to the number of repeating units n of "-Si-(CH3)2-O-" in the dimethylsiloxane (A) of the methylphenyl group-containing polysiloxane.
[0061] The above methylphenyl group-containing polysiloxane is, for example, -80 o It can have a glass transition temperature of less than C. The above methylphenyl group-containing polysiloxane is, for example, -130 o C or higher -80 o It can have a glass transition temperature of less than C.
[0062] The above glass transition temperature is -80 oIf the temperature exceeds C, brittleness may occur, leading to a decrease in airtightness performance. For example, in the case of O-rings used to prevent hydrogen leakage in cryogenic hydrogen storage containers, the operating temperature is -70°C o About 10 times C o It must have a glass transition temperature or crystallization temperature with a safety margin of C or lower, thereby ensuring stability when used in cryogenic environments.
[0063] When the above methylphenyl group-containing polysiloxane has a molecular weight of about 100,000 g / mol, for example, 25 o It may have a first viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C. In addition, the methylphenyl group-containing polysiloxane is, for example, 80 o It can have a second viscosity in the range of 13,000 cP to 15,000 cP at a temperature of C.
[0064] 25 o 80 relative to the first viscosity at a temperature of C o The viscosity reduction rate of the second viscosity at a temperature of C may, for example, be less than 0.8, may be in the range of 0.6 or more and less than 0.8, or may be in the range of 0.7 or more and less than 0.8. The viscosity reduction rate must satisfy less than 0.8 in order to maintain performance at room temperature at high temperature. If the viscosity reduction rate is 0.8 or more, durability problems such as a decrease in adhesive strength or an increase in permanent extrusion reduction rate may occur when manufacturing high-temperature application devices such as sealants, adhesives, rubber, etc.
[0065] The above-mentioned methylphenyl group-containing polysiloxane can be manufactured by the manufacturing method described below. However, this is exemplary, and various manufacturing methods are included within the technical scope of the present invention.
[0066] Method for manufacturing methylphenyl group-containing polysiloxane
[0067] FIG. 1 illustrates a method for manufacturing a methylphenyl group-containing polysiloxane included in a silicone adhesive composition according to one embodiment of the present invention using a chemical formula.
[0068] Referring to FIG. 1, the methylphenyl group-containing polysiloxane may use a siloxane oligomer containing dimethyl siloxane (A) having vinyl groups as both end groups and a methylphenyl siloxane (B) having hydride groups as both end groups that can react with the oligomer to form a linear chain.
[0069] The above methylphenyl group-containing polysiloxane can be formed by the reaction of the vinyl group (CH2=CH-) of the siloxane oligomer and the hydride group (H-) of the methylphenyl siloxane. That is, it can be formed by a hydrosilylation reaction. Accordingly, the above methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (where n is 15 or more and 300 or less). The above repeating unit may be repeated m times (where m is 2 or more and 256 or less). Accordingly, the above methylphenyl group-containing polysiloxane may have a molecular weight of 10,000 g / mol to 1,000,000 g / mol.
[0070] This reaction can be carried out based on a platinum (Pt) catalyst. Here, reactions between vinyl groups or between hydride groups do not occur, and thus it is an excellent reaction for repeatable structure control.
[0071] In the above methylphenyl group-containing polysiloxane, control of the phenyl group structure within the polysiloxane for improving low-temperature performance can be achieved through step polymerization of a dimethyl siloxane oligomer and a methylphenyl siloxane monomer.
[0072] FIG. 2 is a flowchart illustrating a method for manufacturing a methylphenyl group-containing polysiloxane included in a silicone adhesive composition according to an embodiment of the present invention.
[0073] Referring to FIG. 2, a method for manufacturing a polysiloxane containing a methylphenyl group (S100) comprises the steps of: stirring a siloxane oligomer and a retardant to form a first mixture (S110); stirring the first mixture and methylphenyl siloxane to form a second mixture (S120); stirring the second mixture and a platinum catalyst to form a third mixture (S130); and heating the third mixture to polymerize the siloxane oligomer and the methylphenyl siloxane (S140).
[0074] Before performing the step (S110) of forming the first mixture, a step of nitrogen purging of the reaction vessel containing the siloxane oligomer and the retardant may be further performed. Impurities and moisture present in the reaction vessel can be removed by such nitrogen purging.
[0075] The step (S110) of forming the first mixture above can be performed by introducing a siloxane oligomer and a retardant into the reaction vessel and stirring to form the first mixture in which the siloxane oligomer and the retardant are mixed.
[0076] In the step (S110) of forming the first mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0077] The above retardant may be added in a range of 0.01 g to 0.5 g based on 100 g of the above siloxane oligomer, for example. The above retardant may be added in an amount of 0.1 g (i.e., 0.1 phr) based on 100 g of the above siloxane oligomer, for example.
[0078] The above retardant may include, for example, at least one of a phenolic compound, a nitroxy radical compound, an aromatic amine compound, and a sulfur compound. The above retardant may include, for example, at least one of 1-ethylcyclohexanol, hydroquinone (HQ), tert-butylhydroquinone (TBHQ), para-methoxyphenol, 1,2-dihydroxybenzene, 2,2,6,6-tetramethylpiperidine-1-oxyl, phenylene diamine, N,N'-diphenyl-p-phenylenediamine (DPPD), thiourea, and alkyl thiophenol.
[0079] The step (S120) of forming the second mixture may be performed by introducing methylphenylsiloxane into the reaction vessel and stirring the first mixture and the methylphenylsiloxane to form the second mixture in which the siloxane oligomer, the retardant, and the methylphenylsiloxane are mixed.
[0080] In the step (S120) of forming the second mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0081] The step (S130) of forming the third mixture may be performed by introducing a platinum catalyst into the reaction vessel and stirring the second mixture and the platinum catalyst to form the third mixture in which the siloxane oligomer, the retardant, the methylphenylsiloxane, and the platinum catalyst are mixed.
[0082] In the step (S130) of forming the third mixture, the stirring may be performed, for example, for 1 minute to 20 minutes, and for example, for about 10 minutes. The stirring is performed at room temperature, for example, 0 o C to 40 o It can be performed at a temperature in the C range.
[0083] The platinum catalyst can promote the hydrosilylation reaction. The platinum catalyst may be a material formed based on platinum. The platinum catalyst may include, for example, at least one of a Speier catalyst composed of a platinum-chloroplatinic acid-alcohol solution, a Karstedt catalyst composed of a platinum-divinyltetramethyldisiloxane complex, and an Ashby catalyst composed of a platinum-allyl complex.
[0084] The platinum catalyst may be added in an amount ranging from, for example, 0.01 g to 0.1 g based on 100 g of the siloxane oligomer. The platinum catalyst may be added in an amount of, for example, 0.05 g (i.e., 0.05 phr) based on 100 g of the siloxane oligomer.
[0085] The above polymerization step (S140) is, for example, 60 o C to 120 o It can be performed at a temperature in the C range. For example, the polymerization step (S150) may be performed using a reaction vessel containing the second mixture, for example, 60 o C to 120 oIt can be formed by heating the second mixture by placing it in an oil bath maintained at a temperature in the range of C and maintaining it for 1 minute to 10 hours, thereby polymerizing the siloxane oligomer and the methylphenylsiloxane.
[0086] By the above polymerization step (S140), a methylphenyl group-containing polysiloxane can be formed.
[0087] The amount of methylphenylsiloxane added can be controlled according to the molecular weight of the siloxane oligomer.
[0088] For example, the amount (g) of the above-mentioned methylphenylsiloxane can be calculated according to the following formula.
[0089] Amount of methylphenylsiloxane added = (Weight of siloxane oligomer / Molecular weight of siloxane oligomer) x (1 / 2) x (Molecular weight of methylphenylsiloxane)
[0090] The molecular weight of the above methylphenylsiloxane is 270.55 g / mol.
[0091] When the molecular weight of the above siloxane oligomer is 2306 g / mol, the value of n is 29 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 5.87 g. The content of the above methylphenylsiloxane is approximately 1.7 mol% when calculated as 1 / (29 x 2 + 1) x 100.
[0092] When the molecular weight of the above siloxane oligomer is 6832 g / mol, the value of n is 90 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 1.98 g. The methylphenylsiloxane is 1 mole. The content of the methylphenylsiloxane is approximately 0.55 mol% when calculated as 1 / (90x2+1)x 100.
[0093] When the molecular weight of the above siloxane oligomer is 24061 g / mol, the value of n is 322 moles, and the methylphenylsiloxane is 1 mole. In this case, the amount of methylphenylsiloxane added per 100 g of the above siloxane oligomer is 0.56 g. The methylphenylsiloxane is 1 mole. The content of the methylphenylsiloxane is approximately 0.16 mol% when calculated as 1 / (322 x 2 + 1) x 100.
[0094] After performing the polymerization step (S140) above, the polymerization reaction can be repeated by adding methylphenylsiloxane to the polymerized polysiloxane formed to form a polysiloxane having a desired molecular weight. If necessary, a retardant and a platinum catalyst may be further added. This may be referred to as step polymerization.
[0095] The above methylphenyl group-containing polysiloxane can be formed by step polymerization. Accordingly, the total molecular weight of the methylphenyl group-containing polysiloxane can be determined according to the number of step polymerizations.
[0096] A first polysiloxane can be formed by first polymerizing the above siloxane oligomer and the above methylphenylsiloxane, and a second polysiloxane can be formed by second polymerizing the first polysiloxane and the added methylphenylsiloxane to form a second polysiloxane in which the first polysiloxane is chemically bonded by the added methylphenylsiloxane. In this way, a third polysiloxane can be formed by tertiarily polymerizing the second polysiloxane and the added methylphenylsiloxane, and an n-th polysiloxane can be formed by repeating the process to perform n-th polymerization.
[0097] For example, we will describe a case where the methylphenylsiloxane is 2 mol% and the number average molecular weight (Mn) of the methylphenyl group-containing polysiloxane is about 100,000 g / mol. As a first step, when the siloxane oligomer having a molecular weight of 2306 g / mol and a structure of An is reacted with the methylphenylsiloxane, a first material having a structure of AnBAn having two terminals of a vinyl group is formed, and the number average molecular weight may be about 4883 g / mol. As a second step, when the first material is reacted again with the methylphenylsiloxane, a second material having a structure of AnBAnBAnBAn is formed, and the number average molecular weight may be about 10,036 g / mol. If this is repeated, the number average molecular weight of the substance formed in the third step may be about 20,342 g / mol, the number average molecular weight of the substance formed in the fourth step may be about 40,954 g / mol, and the number average molecular weight of the substance formed in the fifth step may be 82,179 g / mol.
[0098] The above number average molecular weight is based on theoretical calculations, and a material having a deviation of approximately 10% to 20% may be produced depending on experimental conditions.
[0099] Below, experimental examples of polysiloxanes containing methylphenyl groups will be described.
[0100] Experimental example for methylphenyl group-containing polysiloxane
[0101] Preferred experimental examples are presented below to aid in understanding the present invention. However, the following experimental examples are intended only to aid in understanding the present invention and do not limit the present invention. Details not described herein can be sufficiently technically inferred by those skilled in the art, so their description is omitted.
[0102] Experimental examples were manufactured in the following manner.
[0103] A flask was used as a reaction vessel, and moisture and impurities present inside the flask were removed by purging with nitrogen. 100 g of siloxane oligomer and 0.5 phr (0.5 g) of 1-ethylcyclohexanol as a retardant relative to the siloxane oligomer were added to the flask. Subsequently, at room temperature (25 o A first mixture was formed by stirring at 150 rpm with a mechanical stirrer equipped with a Teflon impeller for 10 minutes in C.
[0104] Next, 5.87 g of methylphenylsiloxane was added to the first mixture. Then, at room temperature (25 o A second mixture was formed by stirring at 150 rpm with a mechanical stirrer equipped with a Teflon impeller for 10 minutes in C).
[0105] Next, a platinum catalyst (HA-04C, SI Feliz Co.) was added to the second mixture at a concentration of 0.05 phr (0.05 g) relative to the siloxane oligomer. Subsequently, the mixture was brought to room temperature (25 o A third mixture was formed by stirring in C) for 10 minutes.
[0106] Subsequently, the above third mixture 80 o Polysiloxane was formed by charging it into an oil bath of C and maintaining it for 2 hours to induce a polymerization reaction.
[0107] Subsequently, the step of mixing the manufactured polysiloxane, a retardant, diphenylsiloxane, and a platinum catalyst, followed by a polymerization reaction, was repeated to form experimental examples according to the diphenyl content. Among the following experimental examples, Experimental Example 1 and Experimental Example 2 are included within the scope of the present invention.
[0108] Experimental Example 1 had a molecular weight of 2306 g / mol of the initially added siloxane oligomer, and the content of methylphenylsiloxane in the polysiloxane prepared accordingly was 1.7 mol%.
[0109] Experimental Example 2 had a molecular weight of siloxane oligomer of 6832 g / mol, and accordingly, the content of methylphenylsiloxane in the polysiloxane was 0.55 mol%.
[0110] Experimental Example 3 was performed in the same manner as Experimental Example 1, except that methylphenylsiloxane was not added and only siloxane oligomer was added, to form polysiloxane.
[0111] Experimental Examples 4 and 5 used commercially available materials from GEOKO. The methylphenylsiloxane content in Experimental Example 4 was 5 mol%, and the methylphenylsiloxane content in Experimental Example 5 was 10 mol%. Experimental Examples 4 and 5 are formed using a ring opening method.
[0112] Experimental Example 6 was performed in the same manner as the example to form polysilicon, except that the molecular weight of the siloxane oligomer was 24061 g / mol, and accordingly, the content of methylphenylsiloxane in the polysiloxane was 0.2 mol%.
[0113] The repeating unit of the polysiloxane prepared is AnB for Experimental Example 1, Experimental Example 2, and Experimental Example 6, A for Experimental Example 3, and AABB for Experimental Examples 4 and 5. Here, A is dimethyl siloxane and B is methyl phenyl siloxane.
[0114] The molecular weights of the examples and comparative examples were all at the level of approximately 100,000 g / mol. This was selected because using polysiloxane with a molecular weight of 100,000 g / mol offers excellent flowability and processability in products such as sealants, adhesives, and rubber.
[0115] The examples and comparative examples all included vinyl groups at both ends.
[0116] The glass transition temperature of the above polysiloxane was measured using a TA DSC 250. The measurement method is as follows: 50 o-85 in C o After primary cooling to C, wait 10 minutes, and -85 o 50 in C o After heating to C for the first time, wait 10 minutes, and 50 o -85 in C o After secondary cooling to C, wait 10 minutes, and -85 o 50 in C o During the process of waiting 10 minutes after heating a second time to C, 5 o It was performed by scanning at a speed of C / min.
[0117] The viscosity of the above polysiloxane is 25 o It was measured in C.
[0118] The viscosity of the above polysiloxane was measured using a cone-plate type rotational viscometer (Visco QC300H, Anton Paar). After setting the sampler temperature, 0.5 ml of the sample was aliquoted and sampled, and then the rotational speed (rpm) was set so that the torque value reached 70~80%, and the viscosity value was measured and acquired.
[0119] Table 1 shows the characteristics of methylphenyl group-containing polysiloxanes.
[0120] division Repetitive unit Methylphenylsiloxane content (mol%) glass transition temperature 25 o C viscosity (cP) Experimental Example 1 AnB 2 -80 o Less than C 69,890 Experimental Example 2 AnB 1 -80 o Less than C 67,140 Experimental Example 3 A 0 -42 o C 65,000 Experimental Example 4 AABB 5 -42 o C 73,490 Experimental Example 5 AABB 10 -80 o Less than C 79,640 Experimental Example 6 AnB 0.16 -45 o C 66,500
[0121] Referring to Table 1, the examples are -80 o Satisfies a glass transition temperature of less than C, and 25 o It satisfies a viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C.
[0122] Experimental Example 3 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention.
[0123] Experimental Example 4 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention. In addition, Experimental Example 4 is 25 oThe viscosity at temperature C does not satisfy the scope of the present invention.
[0124] For reference, even if methylphenylsiloxane is introduced to improve the low-temperature properties of Experimental Example 3, if the room temperature viscosity increases by more than 10% compared to Experimental Example 3, it may cause solubility problems and processability problems, which may result in limitations on the amount added during the formulation process for manufacturing parts.
[0125] Experimental Example 5 is -80 o It satisfies the glass transition temperature of the present invention of less than C. However, there is a limitation in that it must contain 10% by weight of expensive methylphenylsiloxane for this purpose. In addition, Experimental Example 5 is 25 o The viscosity at temperature C does not satisfy the scope of the present invention.
[0126] Experimental Example 6 has a glass transition temperature of -80 o It is higher than C and does not satisfy the glass transition temperature range of the present invention. However, Experimental Example 6 is 25 o It satisfies a viscosity in the range of 63,000 cP to 70,000 cP at a temperature of C. Accordingly, the methylphenyl content needs to exceed 0.2 weight%.
[0127] Silicone adhesive composition
[0128] A silicone adhesive composition according to one embodiment of the present invention comprises: a first crosslinker comprising a first crosslinked network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinker comprising a second crosslinked network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, wherein the first crosslinked network and the second crosslinked network constitute an interpenetrating dual network structure.
[0129] By means of this interpenetrating dual network structure, the cohesiveness, structural stability, elastic recovery, and low-temperature properties of the silicone adhesive composition can be improved.
[0130] The above methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit may be AnB (wherein n is 15 or more and 300 or less).
[0131] In the above methylphenyl group-containing polysiloxane, the fraction of methylphenyl groups may be in the range of 0.5 mol% to 5 mol%.
[0132] As the above-mentioned methylphenyl group-containing polysiloxane is as described above, a detailed description will be omitted.
[0133] The vinyl group of the above methylphenyl group-containing polysiloxane can be crosslinked by performing a hydrosilylation reaction with the Si-H group of the monomeric first siloxane-based crosslinking agent, thereby forming the first crosslinking network. The first crosslinking network may have a partially crosslinked random structure.
[0134] The above polysiloxane adhesive resin may include at least one vinyl group at both ends or at least one end to enable a crosslinking reaction. The vinyl group can form crosslinking bonds by performing a hydrosilylation reaction with the Si-H group of a siloxane-based crosslinking agent. Accordingly, the polysiloxane adhesive resin can form a second crosslinking network with a network structure.
[0135] In addition, the second crosslinking network can be crosslinked with the first crosslinking network formed by the methylphenyl group-containing polysiloxane and interconnected to realize an interpenetrating dual network structure. Accordingly, the cohesive strength, structural stability, and elastic recovery of the silicone adhesive composition can be improved.
[0136] The above polysiloxane adhesive resin may include a polysiloxane material as a silicone gum material. The polysiloxane material included in the above polysiloxane adhesive resin may be a linear polymer and may include vinyl groups at both ends or at least one end. The above polysiloxane material may have a molecular weight of, for example, 10,000 g / mol to 800,000 g / mol. The above polysiloxane material may be a mixture of materials having various molecular weights, rather than a mixture of materials with a single molecular weight.
[0137] The above polysiloxane adhesive resin may include, for example, at least one of polydimethylsiloxane (PDMS), dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer.
[0138] The above polysiloxane adhesive resin may further comprise a resin composed of a network-type oligomer and having vinyl groups or hydride groups at the ends. The resin may have a ladder structure or a random structure. The resin may be referred to as MQ resin. The MQ resin is M unit (R3SiO 1 / 2 It may be a siloxane-based resin containing ) and Q units (SiO4 / 2). In the polysiloxane adhesive resin, the weight ratio of the polysiloxane material and the resin may be in the range of 10:1 to 1:10.
[0139] The above silicone adhesive composition may further include a crosslinking agent, for example, a first siloxane-based crosslinking agent and a second siloxane-based crosslinking agent.
[0140] The first siloxane-based crosslinking agent may include a single-molecule crosslinking agent having a siloxane backbone. The single-molecule siloxane-based crosslinking agent may have a non-polymeric siloxane structure that does not have repeating units. Therefore, it can be distinguished from chain-type polysiloxanes having repeating units.
[0141] In addition, the above-mentioned monomolecular siloxane-based crosslinking agent may have a branched structure in which a plurality of hydroxysiloxane groups (Si-H) are bonded to a central siloxane backbone, and through this, it may react with a plurality of polysiloxane chains.
[0142] For example, the first siloxane-based crosslinking agent may include a structure in which a plurality of Si-H groups are bonded to a single central silicon backbone, and the Si-H groups may partially interconnect a plurality of polysiloxane chains by performing a hydrosilylation reaction with the vinyl groups of the methylphenyl group-containing polysiloxane. Accordingly, the methylphenyl group-containing polysiloxane may be crosslinked to form a first crosslinking network with a partially crosslinked random structure. In addition, the first crosslinking network has a structure in which the polysiloxane chains are partially connected, thereby enabling uniformly dispersed crosslinking points while maintaining the mobility of the siloxane chains.
[0143] In addition, the first cross-linked network can improve the connectivity between siloxane chains, thereby enhancing stress distribution characteristics, structural stability, and elastic recovery characteristics. Furthermore, since the first cross-linked network can suppress excessive movement of siloxane chains or local network collapse, excellent flexibility, adhesive reliability, and low-temperature characteristics can be maintained even in environments of repeated deformation and low temperature.
[0144] The first siloxane-based crosslinking agent may include a monomolecular siloxane-based crosslinking agent comprising a plurality of Si-H groups on a siloxane backbone, and may include at least one of, for example, branch-type hydrosiloxane, multi-hydride siloxane, and silsesquioxane-based hydrosiloxane.
[0145] The above-mentioned first siloxane-based crosslinking agent may include, for example, a substance having the following chemical formula.
[0146]
[0147] Unlike siloxane chain-type crosslinking agents having repeating units, the above-mentioned monomolecular first siloxane-based crosslinking agent can function to form local crosslinking points by having an independent single-molecule structure. That is, even if the above-mentioned monomolecular first siloxane-based crosslinking agent includes multiple Si-H groups on the siloxane backbone, it can function in a manner that locally connects adjacent polysiloxane chains rather than forming a continuous long-range network like chain-type crosslinking agents.
[0148] Accordingly, the first cross-linked network can form a partially connected, partially cross-linked random structure rather than a continuous three-dimensional network structure, and can more effectively maintain the mobility and free volume of the siloxane chains. In addition, the partially cross-linked structure can provide local cross-linking points while suppressing excessive restraint of the siloxane chains, thereby alleviating stress concentration and suppressing network collapse during repeated deformation. Accordingly, the first cross-linked network can maintain excellent flexibility, elastic recovery, and adhesive reliability even in environments of repeated deformation and low temperature.
[0149] The second siloxane-based crosslinking agent may include a multifunctional crosslinking agent having a siloxane backbone. The multifunctional siloxane-based crosslinking agent may include a plurality of Si-H groups on the siloxane backbone and may interconnect a plurality of polysiloxane chains by performing a hydrosilylation reaction with the vinyl groups of the polysiloxane adhesive resin.
[0150] Accordingly, the polysiloxane adhesive resin can be cross-linked to form a second cross-linked network with a continuous three-dimensional network structure, and a denser and more uniform cross-linked structure can be realized throughout the network. In addition, the second cross-linked network can improve the connectivity between polysiloxane chains, thereby improving stress distribution characteristics, structural stability, and elastic recovery characteristics. Furthermore, since the second cross-linked network can suppress excessive movement of siloxane chains or local network collapse, excellent flexibility, adhesive reliability, and low-temperature characteristics can be maintained even in environments of repeated deformation and low temperature.
[0151] The second cross-linked network can interpenetrate with the first cross-linked network to form an interpenetrating dual network structure, thereby further improving the cohesiveness, structural stability, and low-temperature properties of the silicone adhesive composition.
[0152] The second siloxane-based crosslinking agent may include a siloxane-based crosslinking agent comprising a hydrosiloxane group, and may include at least one of, for example, polyorganohydrosiloxane, methylhydrosiloxane-dimethylsiloxane copolymer, hydride-terminated siloxane, and hydride-functional silicone resin.
[0153] The above second siloxane-based crosslinking agent may include, for example, a substance having the following chemical formula.
[0154]
[0155] A platinum catalyst may be used when forming the above silicone adhesive composition. Accordingly, the platinum catalyst may remain in the silicone adhesive composition or may be removed. The platinum catalyst can be activated by heat to promote the crosslinking reaction between the hydride and the vinyl group. The platinum catalyst may include the material described above. The platinum catalyst may be used to form the first crosslink and the second crosslink.
[0156] The above polysiloxane adhesive resin may include, for example, a material having the following chemical formula.
[0157]
[0158] The above resin may include, for example, a material having the following chemical formula.
[0159]
[0160] The above platinum catalyst may include, for example, a material having the following chemical formula.
[0161]
[0162] The first crosslinker may comprise 0.05 to 0.2 parts by weight of a monomeric first siloxane-based crosslinking agent per 10 parts by weight of the methylphenyl group-containing polysiloxane.
[0163] The molar ratio (Si-H / vinyl mol ratio) of the Si-H groups of the siloxane-based crosslinking agent in the first crosslinked material and the vinyl groups of the methylphenyl group-containing polysiloxane may be a factor for controlling the degree of the crosslinking reaction and the density of the crosslinking network. Depending on the content of the Si-H groups, the final crosslinking density, crosslinking network structure, elasticity, and adhesive properties may change. If the molar ratio is excessively low, the formation of the crosslinking network is insufficient, which may lead to a decrease in cohesiveness and structural stability, and the first crosslinking network may not be sufficiently formed. Consequently, the shape stability and adhesive strength of the adhesive layer may decrease in a low-temperature environment, and the recovery properties after repeated deformation may be reduced. On the other hand, if the molar ratio is excessively high, the crosslinking reaction proceeds excessively, which may increase the crosslinking density of the first crosslinking network. Consequently, brittleness may increase or low-temperature properties may decrease. In addition, the molar ratio of the Si-H groups and the vinyl groups can control the gel fraction and structural stability of the first crosslinking network, thereby controlling the elastic recovery, cohesiveness, and low-temperature properties of the final double network structure. The molar ratio may be, for example, in the range of 0.3 to 1.2.
[0164] The gel fraction of the first crosslinker may refer to the ratio of the insoluble portion remaining without dissolving in the solvent among the polymer network formed after the crosslinking reaction. The gel fraction can be used as an indicator of the degree of crosslinking network formation and crosslinking density, and a higher gel fraction may indicate that a denser crosslinking structure has been formed. For example, if the gel fraction is excessively low, the formation of the crosslinking network is insufficient, which may lead to reduced cohesion and structural stability, and may result in reduced shape stability and recovery properties of the adhesive layer in a low-temperature environment. On the other hand, if the gel fraction is excessively high, excessive crosslinking may reduce the flexibility of the adhesive layer and increase brittleness, thereby degrading low-temperature properties. Therefore, the gel fraction may be an important factor for controlling the network density, elastic recovery, cohesion, and low-temperature properties of an interpenetrating double network structure. The gel fraction may be, for example, in the range of 15% to 65%.
[0165] The second crosslinker may comprise 1 to 5 parts by weight of the first crosslinker and 0.5 to 2 parts by weight of a polyfunctional second siloxane-based crosslinking agent per 100 parts by weight of the polysiloxane adhesive resin.
[0166] In order to maintain adhesive strength at low temperatures and ensure stability, it is desirable for the above silicone adhesive composition to have a low glass transition temperature (Tg) and a high elastic recovery rate.
[0167] In order for the above silicone adhesive composition to be used as an adhesive for displays, electrical and electronic devices, etc., it is desirable that it have a peel strength of at least 8 N / 25 mm. For example, if it is less than 8 N / 25 mm, it may not be possible to maintain the bonding shape of a large display module.
[0168] The above silicone adhesive composition is, for example, -20 o It can have a glass transition temperature of C or lower, for example -20 o C to -50 o It may be in the C range. The glass transition temperature is at least -20 o By having a range of C or lower, the hardening or brittleness of the adhesive layer is suppressed even in low-temperature environments, thereby maintaining excellent adhesive properties and flexibility. On the other hand, in environments below the glass transition temperature, cracks or structural damage may occur in the adhesive layer when external force is applied.
[0169] The above silicone adhesive composition may have an elastic recovery rate of 80% or more, and may be, for example, in the range of 85% or more and 100% or less. The elastic recovery rate may be an indicator representing the degree to which the adhesive layer is restored to its original shape after repeated deformation, and by having a high elastic recovery rate, excellent structural stability and adhesive reliability can be secured even in repeated bending or compression environments. In particular, when the elastic recovery rate is 85% or more, superior recovery characteristics and cohesion can be provided.
[0170] The above silicone adhesive composition may have a peel strength of, for example, 8 N / 25 mm or more, and may be in the range of, for example, 8 N / 25 mm or more and 15 N / 25 mm or less.
[0171] A silicone adhesive film can be formed using the above silicone adhesive composition.
[0172] silicone adhesive film
[0173] A silicone adhesive film according to the technical concept of the present invention may comprise a film substrate; and a silicone adhesive composition applied and cured on the film substrate.
[0174] The above silicone adhesive composition comprises: a first crosslinker comprising a first crosslinked network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinker comprising a second crosslinked network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, wherein the first crosslinked network and the second crosslinked network constitute an interpenetrating dual network structure.
[0175] The above film substrate may include various materials, for example, polymer materials. The above film substrate may include, for example, a fluorinated release film, and the fluorinated release film may include a fluorinated polymer such as PTFE, PVDF, FEP, etc., or may be a film designed to allow adhesives, silicones, resins, etc. to be easily peeled off by applying a fluorinated coating agent such as fluorosilane or PVDF (Polyvinylidene fluoride) to its surface. However, this is exemplary and the technical concept of the present invention is not limited thereto.
[0176] A silicone adhesive film can be manufactured by the following manufacturing method. However, this is exemplary, and various manufacturing methods are included within the technical scope of the present invention.
[0177] Method for manufacturing a silicone adhesive film
[0178] FIG. 3 is a flowchart illustrating a method for manufacturing a silicone adhesive film comprising a methylphenyl group-containing polysiloxane according to an embodiment of the present invention.
[0179] Referring to FIG. 3, a method for manufacturing a silicone adhesive film (S200) comprises the steps of: providing a polysiloxane containing a methylphenyl group (S210); adding the methylphenyl group-containing polysiloxane, a monomolecular first siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a first crosslinking target (S220); crosslinking the first crosslinking target to form a first crosslinked material comprising a first crosslinking network having a partially crosslinked random structure formed by crosslinking the methylphenyl group-containing polysiloxane (S230); adding the first crosslinked material, a polysiloxane adhesive resin, a multifunctional second siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a second crosslinking target (S240); and applying the second crosslinked target onto a film substrate (S250). and a step (S260) of crosslinking the second crosslinking target to form a second crosslinked material comprising a second crosslinked network formed by crosslinking the polysiloxane adhesive resin.
[0180] The first bridge network and the second bridge network form an interpenetrating dual network structure.
[0181] FIG. 4 illustrates a conceptual diagram of the formation of a double network structure of a silicone adhesive film according to an embodiment of the present invention.
[0182] Referring to FIG. 4, a second cross-linking network (20) formed by the second cross-linking agent may be formed inside a first cross-linking network (10) of a partially cross-linked random structure formed by the first cross-linking agent. Accordingly, the first cross-linking network (10) and the second cross-linking network (20) may interpenetrate and connect to form an interpenetrating dual network structure. The interpenetrating dual network structure may be a structure in which the structural stability of the first cross-linking network (10) and the adhesive properties of the second cross-linking network (20) are combined, thereby providing excellent cohesive strength, elastic recovery, and low-temperature properties.
[0183] Referring again to FIG. 3, a method for manufacturing a silicone adhesive film will be described in detail.
[0184] The step (S210) of providing the methylphenyl group-containing polysiloxane can be performed as described above, and specifically may include the step of forming a first mixture by stirring a siloxane oligomer and a retardant; the step of forming a second mixture by stirring the first mixture and the methylphenyl siloxane; the step of forming a third mixture by stirring the second mixture and a platinum catalyst; and the step of polymerizing the siloxane oligomer and the methylphenyl siloxane by heating the third mixture.
[0185] The step (S220) of forming the first crosslinking target can be performed by adding the methylphenyl group-containing polysiloxane, the monomeric first siloxane-based crosslinking agent, and the platinum catalyst to an organic solvent and then stirring to form the first crosslinking target.
[0186] The first siloxane-based crosslinking agent and the platinum catalyst may be added to the organic solvent simultaneously or separately. For example, the first siloxane-based crosslinking agent may be added to the organic solvent and stirred, and then the platinum catalyst may be added to the organic solvent and stirred. Alternatively, conversely, the platinum catalyst may be added to the organic solvent and stirred, and then the first siloxane-based crosslinking agent may be added to the organic solvent and stirred. The stirring may be performed in various ways, for example, using a mechanical stirrer.
[0187] For example, after adding the methylphenyl group-containing polysiloxane and the first siloxane-based crosslinking agent to the organic solvent, at room temperature, for example, 0 o C to 40 o After stirring for 1 to 30 minutes at a temperature in the range of C, the platinum catalyst is further added to the organic solvent and stirred at room temperature, for example, 0 o C to 40 o The first crosslinking target can be formed by further stirring for 1 to 30 minutes at a temperature in the range of C.
[0188] The above organic solvent can uniformly dissolve and disperse the mixed materials and control the viscosity of the mixture to improve the uniformity of the crosslinking reaction. The above organic solvent may be, for example, at least one of xylene, toluene, benzene, ethylbenzene, isopropylbenzene, 1,3,5-trimethylbenzene, hexane, heptane, isoparaffin, and cyclohexane.
[0189] The step of forming the first crosslink (S230) can be performed by crosslinking the first crosslink target to form a first crosslink comprising a first crosslink network having a partially crosslinked random structure formed by crosslinking the methylphenyl group-containing polysiloxane.
[0190] For example, the above-mentioned first crosslinking target, for example 80 o C to 120 o The first crosslinker can be formed by placing it in an oil bath maintained at a temperature in the C range and maintaining it for 30 minutes to 2 hours to allow a crosslinking reaction. For example, 100 o It can be performed for 1 hour at a temperature of C.
[0191] The step (S240) of forming the second crosslinking target can be performed by adding the first crosslinking material, the polysiloxane adhesive resin, the multifunctional second siloxane-based crosslinking agent, and the platinum catalyst to an organic solvent and then stirring to form the second crosslinking target.
[0192] The second siloxane-based crosslinking agent and the platinum catalyst may be added to the organic solvent simultaneously or separately. For example, the second siloxane-based crosslinking agent may be added to the organic solvent and stirred, and then the platinum catalyst may be added to the organic solvent and stirred. Alternatively, conversely, the platinum catalyst may be added to the organic solvent and stirred, and then the second siloxane-based crosslinking agent may be added to the organic solvent and stirred. The stirring may be performed in various ways, for example, using a mechanical stirrer.
[0193] For example, after adding the first crosslinker, the polysiloxane adhesive resin, and the second siloxane-based crosslinking agent to an organic solvent, at room temperature, for example, 0 o C to 40 oAfter stirring for 1 to 30 minutes at a temperature in the range of C, the platinum catalyst is further added to the organic solvent and stirred at room temperature, for example, 0 o C to 40 o The second crosslinking target can be formed by further stirring for 1 to 30 minutes at a temperature in the range of C.
[0194] The above-mentioned application step (S250) may be performed by applying the second crosslinking target onto a film substrate.
[0195] The above coating may be performed by at least one of the following methods: drop coating, spin coating, drawdown coating, Mayer bar coating, doctor blade coating, slot die coating, dip coating, spray coating, inkjet coating, and roll coating.
[0196] The step of forming the second crosslink (S260) can be achieved by crosslinking the second crosslinking target to form a second crosslink comprising a second crosslinking network formed by crosslinking the polysiloxane adhesive resin. Accordingly, the first crosslinking network and the second crosslinking network can form an interpenetrating dual network structure. Accordingly, a silicone adhesive film can be completed.
[0197] In the step (S260) of forming the secondary crosslinker, residual volatile substances are removed by heat, thereby stabilizing the physical properties of the silicone adhesive film, and additional crosslinking reactions of residual reactive species are induced, thereby stabilizing the crosslinking network.
[0198] The step of forming the secondary crosslinker (S260) is, for example, 120 o C to 140 o The second crosslinker can be formed by performing a crosslinking reaction by maintaining it in an oven maintained at a temperature in the C range for 1 to 30 minutes. For example, 130 o It can be performed for 10 minutes at a temperature of C.
[0199] Accordingly, the first cross-linked network acts as a structural support, and the second cross-linked network provides adhesive properties, thereby enabling excellent cohesive strength and elastic recovery properties.
[0200] The first crosslinking target may comprise, with respect to 100 parts by weight of an organic solvent, 5 to 20 parts by weight of the methylphenyl group-containing polysiloxane, 0.05 to 0.2 parts by weight of the first siloxane-based crosslinking agent, and 0.005 to 0.1 parts by weight of a platinum catalyst.
[0201] The second crosslinking target may comprise, with respect to 100 parts by weight of an organic solvent, 1 to 5 parts by weight of the first crosslinking material, 95 to 99 parts by weight of a polysiloxane adhesive resin, 0.5 to 2 parts by weight of a second siloxane-based crosslinking agent, and 0.1 to 2 parts by weight of a platinum catalyst.
[0202] Experimental example for silicone adhesive film
[0203] Preferred experimental examples are presented below to aid in understanding the present invention. However, the following experimental examples are intended only to aid in understanding the present invention and do not limit the present invention. Details not described herein can be sufficiently technically inferred by those skilled in the art, so their description is omitted.
[0204] Table 2 shows the composition and component content for forming the first crosslink of the silicone adhesive film according to the present invention.
[0205] division polysiloxane 1st crosslinking agent (g) Si-H / Vinyl molar ratio platinum catalyst (g) xylene solvent (g) Gel fraction (%) Content (g) Molecular weight (g / mol) repeating unit structure Methylphenyl fraction (mol%) Example 1 10 10000 AnB 2 0.05 0.3 0.01 100 18 Example 2 10 10000 AnB 2 0.1 0.6 0.01 100 38 Example 3 10 10000 AnB 2 0.2 1.2 0.01 100 62 Comparative Example 1 0 - - - - - - - Comparative Example 2 10 10000 A 0 0.1 0.6 0.01 100 45 Comparative Example 3 10 10000 A 0 0.2 1.2 0.01 100 68 Comparative Example 4 10 10000 AABB 5 0.1 0.6 0.01 100 34 Comparative Example 5 10 10000 AABB 5 0.2 1.2 0.01 100 52
[0206] Table 3 shows the composition and component content for forming the second crosslink of the silicone adhesive film according to the present invention.
[0207] First crosslinker (g) Polysiloxane adhesive resin (g) Second crosslinking agent (g) platinum catalyst (g) xylene solvent (g) Example 1 3 97 1 0.5 100 Example 2 3 97 1 0.5 100 Example 3 3 97 1 0.5 100 Comparative Example 1 0 97 1 0.5 100 Comparative Example 2 3 97 1 0.5 100 Comparative Example 3 3 97 1 0.5 100 Comparative Example 4 3 97 1 0.5 100 Comparative Example 5 3 97 1 0.5 100
[0208] Referring to Tables 2 and 3, Examples 1 to 3 correspond to cases where a methylphenyl group-containing polysiloxane having an AnB repeating unit is included as the siloxane, and the fraction of the methylphenyl group is set to 2 mol%.
[0209] Examples 1 to 3 differ in the content of the first crosslinking agent and the resulting Si-H / vinyl group molar ratio. Specifically, Example 1 contains 0.05 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 0.3, Example 2 contains 0.1 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 0.6, and Example 3 contains 0.2 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 1.2.
[0210] Comparative Example 1 is a case in which a silicone adhesive composition is formed using only a polysiloxane adhesive resin without forming a first crosslinker. That is, it corresponds to a case in which a first crosslinking network by a methylphenyl group-containing polysiloxane is not formed.
[0211] Comparative Examples 2 and 3 correspond to cases where dimethylsiloxane having an A repeating unit is included as the siloxane. Since Comparative Examples 2 and 3 do not include methylphenyl groups, the fraction of methylphenyl groups is 0 mol%.
[0212] In addition, Comparative Example 2 and Comparative Example 3 differ in the content of the first crosslinking agent and the resulting Si-H / vinyl group molar ratio. Specifically, Comparative Example 2 contains 0.1 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 0.6, and Comparative Example 3 contains 0.2 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 1.2.
[0213] Comparative Examples 4 and 5 correspond to cases where a methylphenyl group-containing polysiloxane having an AABB repeating structure is included as the siloxane, and the fraction of the methylphenyl group is set to 5 mol%.
[0214] In addition, Comparative Example 4 and Comparative Example 5 differ in the content of the first crosslinking agent and the resulting Si-H / vinyl group molar ratio. Specifically, Comparative Example 4 contains 0.1 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 0.6, and Comparative Example 5 contains 0.2 g of the first crosslinking agent and has a Si-H / vinyl group molar ratio of 1.2.
[0215] The silicone adhesive film was manufactured as follows.
[0216] After adding xylene to the flask, the methylphenyl group-containing polysiloxane and the first siloxane-based crosslinking agent are added, and the mixture is stirred at room temperature (25) using a mechanical stirrer. o Stirred for 10 minutes at C). Afterwards, additional platinum catalyst was added to the flask and stirred at room temperature (25 o C) was stirred for another 10 minutes. Then, the flask was 100 o The first crosslinked product was prepared by placing it in an oil bath maintained at C and crosslinking it for 1 hour.
[0217] Next, after adding xylene to another flask, the first crosslinking agent, polysiloxane adhesive resin, and second crosslinking agent are added, and heated to room temperature (25) with a mechanical stirrer. o Stirred for 10 minutes at C). Afterwards, additional platinum catalyst was added to the flask and stirred at room temperature (25 oThe second crosslinking target was prepared by stirring for 10 minutes in C).
[0218] After applying the above second crosslinking target as a droplet onto a fluorine release film, it was uniformly coated using the Meyer bar coating method (#5).
[0219] The fluorine release film coated with the above second crosslinking target is 130 o A silicone adhesive film was prepared by placing it in an oven maintained at C and crosslinking it for 10 minutes.
[0220] The glass transition temperature of the above silicone adhesive film was measured using a TA DSC 250. The measurement method is 50 o -85 in C o After primary cooling to C, wait 10 minutes, and -85 o 50 in C o After heating to C for the first time, wait 10 minutes, and 50 o -85 in C o After secondary cooling to C, wait 10 minutes, and -85 o 50 in C o During the process of waiting 10 minutes after heating a second time to C, 5 o It was performed by scanning at a speed of C / min.
[0221] The elastic recovery rate of the above silicone adhesive film was measured using a rheometer in accordance with ASTM D7405-20.
[0222] Table 4 is a table comparing the glass transition temperature, elastic recovery rate, and peel strength of a silicone adhesive film according to an embodiment of the present invention with that of a comparative example.
[0223] division Glass transition temperature ( o C) Elastic recovery rate (%) Peel strength (N / 25 mm) Example 1 -34 90 11.5 Example 2 -28 87 10.2 Example 3 -20 85 8.8 Comparative Example 1 30 76 6.5 Comparative Example 2 27 78 7.2 Comparative Example 3 32 74 6.0 Comparative Example 4 -30 72 9.5 Comparative Example 5 -22 67 8.0
[0224] Referring to Table 4, Examples 1 to 3 are all -20 o It exhibited a glass transition temperature (Tg) of C or lower, a peel strength of 8 N / 25 mm or higher, and an elastic recovery rate of 85% or higher.
[0225] Therefore, the examples confirmed that excellent flexibility, recovery characteristics, and peel stability could be secured even in low-temperature environments, and satisfied the ranges of low-temperature characteristics, elastic recovery characteristics, and peel strength proposed in the present invention.
[0226] In particular, Example 1 corresponds to the case where the content of the first crosslinking agent is lowest when forming the first crosslinker, and the lowest glass transition temperature is -34 o C was shown. This is believed to be because the mobility of the siloxane chains was better maintained due to the relatively low crosslinking density. Meanwhile, the elastic recovery rates of Examples 1 to 3 were all at a similar level of 85% or higher, and excellent structural recovery characteristics were maintained.
[0227] On the other hand, Comparative Examples 1 to 3 are each 30 o C, 27 o C, and 32 o The glass transition temperature of C was shown, and it did not satisfy the low-temperature characteristic range proposed in the present invention. In addition, the elastic recovery rate was also 76%, 78%, and 74%, respectively, showing a value of less than 80%. Furthermore, the peel strength was 6.5 N / 25 mm, 7.2 N / 25 mm, and 6.0 N / 25 mm, respectively, showing a value of less than 8 N / 25 mm. This is judged to be because, when methylphenyl groups are not included, the crystallization behavior of the siloxane chain is not effectively controlled, and sufficient flexibility, recovery characteristics, and peel stability at low temperatures cannot be secured.
[0228] In addition, since Comparative Examples 4 and 5 contain a methylphenyl group, each -30 o C and -22 oThe glass transition temperature of C was shown, satisfying the scope of the present invention in terms of low-temperature characteristics. However, the elastic recovery rates were found to be 72% and 67%, respectively, failing to satisfy the range proposed in the present invention. This is attributed to the fact that in the case of the AABB repeating structure, the elastic recovery characteristics were reduced due to decreased interconnectivity and network uniformity between the first and second cross-linked networks. On the other hand, the peel strength satisfied the scope of the present invention.
[0229] For reference, the AABB repeating structure has the following chemical formula.
[0230]
[0231] Accordingly, it was confirmed that when an interpenetrating dual network structure is formed using a methylphenyl group-containing polysiloxane having AnB repeating units as in the present invention, low-temperature properties, elastic recovery properties, and peel stability can be simultaneously improved. This implies that the arrangement structure of the methylphenyl groups can influence the formation behavior of the cross-linked network and network uniformity. In particular, it is determined that the AnB repeating units of the present invention induce uniform distribution of network stress, thereby maintaining high recovery properties even after repeated deformation.
[0232] It will be obvious to those skilled in the art that the technical concept of the present invention described above is not limited to the aforementioned embodiments and attached drawings, and that various substitutions, modifications, and changes are possible within the scope of the technical concept of the present invention. Accordingly, the scope of rights of the present invention should be determined by the claims set forth below.
Claims
Claim 1 A first crosslinker comprising a first crosslinked network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinker comprising a second crosslinked network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, wherein the first crosslinked network and the second crosslinked network constitute an interpenetrating dual network structure, and the methylphenyl group-containing polysiloxane has the following chemical formula. (Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) Silicone adhesive composition. Claim 2 A silicone adhesive composition according to claim 1, wherein the methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit is AnB (wherein n is 15 or more and 300 or less). Claim 3 delete Claim 4 A silicone adhesive composition according to claim 1, wherein the fraction of methylphenyl groups in the methylphenyl group-containing polysiloxane is in the range of 0.5 mol% to 5 mol%. Claim 5 A silicone adhesive composition according to claim 1, wherein the methylphenyl group-containing polysiloxane has a molecular weight of 10,000 g / mol to 1,000,000 g / mol. Claim 6 In claim 1, the silicone adhesive composition is -20 o C to -50 o A silicone adhesive composition having a glass transition temperature in the C range, an elastic recovery rate of 80% or more, and a peel strength of 8 N / 25 mm or more and 15 N / 25 mm or less. Claim 7 A silicone adhesive composition according to claim 1, wherein the first crosslinker comprises 0.05 to 0.2 parts by weight of a monomeric first siloxane-based crosslinker per 10 parts by weight of the methylphenyl group-containing polysiloxane, and the second crosslinker comprises 1 to 5 parts by weight of the first crosslinker and 0.5 to 2 parts by weight of a polyfunctional second siloxane-based crosslinker per 100 parts by weight of the polysiloxane adhesive resin. Claim 8 A silicone adhesive composition according to claim 1, wherein the first crosslinker has a molar ratio (Si-H / vinyl mol ratio) of the Si-H groups of the siloxane-based crosslinker in the range of 0.3 to 1.2 and the vinyl groups of the methylphenyl group-containing polysiloxane, and has a gel fraction in the range of 15% to 65%. Claim 9 A silicone adhesive composition according to claim 1, wherein the polysiloxane adhesive resin comprises at least one of polydimethylsiloxane (PDMS), dimethyl polysiloxane, dimethyl diphenyl polysiloxane, dimethyl-methylphenyl polysiloxane, polymethylphenylsiloxane, dimethylsiloxane-methylphenylsiloxane copolymer, and dimethylsiloxane-diphenylsiloxane copolymer. Claim 10 A silicone adhesive composition according to claim 1, wherein the polysiloxane adhesive resin further comprises a resin composed of a network-type oligomer and having a vinyl group or a hydride group at the terminal end. Claim 11 The silicone adhesive composition according to claim 1 further comprises: a first siloxane-based crosslinking agent comprising at least one of branch-type hydrosiloxane, multi-hydride siloxane, and silsesquioxane-based hydrosiloxane; and a second siloxane-based crosslinking agent comprising at least one of polyorganohydrosiloxane, methylhydrosiloxane-dimethylsiloxane copolymer, hydride-terminated siloxane, and hydride-functional silicone resin. Claim 12 A film substrate; and a silicone adhesive composition applied and cured on the film substrate, wherein the silicone adhesive composition comprises: a first crosslinker comprising a first crosslinked network having a partially crosslinked random structure formed by crosslinking a methylphenyl group-containing polysiloxane; and a second crosslinker comprising a second crosslinked network formed by crosslinking a polysiloxane adhesive resin having at least one vinyl group, wherein the first crosslinked network and the second crosslinked network constitute an interpenetrating dual network structure, and the methylphenyl group-containing polysiloxane has the following chemical formula. (wherein, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) silicone adhesive film. Claim 13 A silicone adhesive film according to claim 12, wherein the methylphenyl group-containing polysiloxane comprises dimethyl siloxane (A); and methylphenyl siloxane (B) chemically bonded to the dimethyl siloxane, and the repeating unit is AnB (wherein n is 15 or more and 300 or less). Claim 14 In claim 12, the silicone adhesive composition is -20 o C to -50 o Silicone adhesive film having a glass transition temperature in the C range, an elastic recovery rate of 80% or more, and a peel strength of 8 N / 25 mm or more and 15 N / 25 mm or less. Claim 15 The method comprises the steps of: providing a methylphenyl group-containing polysiloxane; adding the methylphenyl group-containing polysiloxane, a monomeric first siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a first crosslinking target; crosslinking the first crosslinking target to form a first crosslinked product comprising a first crosslinking network having a partially crosslinked random structure formed by crosslinking the methylphenyl group-containing polysiloxane; adding the first crosslinked product, a polysiloxane adhesive resin, a polyfunctional second siloxane-based crosslinking agent, and a platinum catalyst to an organic solvent and stirring to form a second crosslinking target; applying the second crosslinking target onto a film substrate; and crosslinking the second crosslinking target to form a second crosslinked product comprising a second crosslinking network formed by crosslinking the polysiloxane adhesive resin, wherein the methylphenyl group-containing polysiloxane has the following chemical formula. (Here, n is 15 or more and 300 or less, and m is 2 or more and 256 or less) Method for manufacturing a silicone adhesive film. Claim 16 A method for manufacturing a silicone adhesive film according to claim 15, wherein the first cross-linking network and the second cross-linking network form an interpenetrating double network structure. Claim 17 A method for manufacturing a silicone adhesive film according to claim 15, wherein the first crosslinking target comprises, with respect to 100 parts by weight of an organic solvent, 5 to 20 parts by weight of the methylphenyl group-containing polysiloxane, 0.05 to 0.2 parts by weight of a first siloxane-based crosslinking agent, and 0.005 to 0.1 parts by weight of a platinum catalyst, and the second crosslinking target comprises, with respect to 100 parts by weight of an organic solvent, 1 to 5 parts by weight of the first crosslinking agent, 95 to 99 parts by weight of a polysiloxane adhesive resin, 0.5 to 2 parts by weight of a second siloxane-based crosslinking agent, and 0.1 to 2 parts by weight of a platinum catalyst. Claim 18 In claim 15, the step of forming the first crosslinking material comprises 80 of the first crosslinking target material o C to 120 o The step of forming the second crosslinker, which is carried out by a crosslinking reaction at a temperature in the C range, comprises 120 of the second crosslinker target. o C to 140 o A method for manufacturing a silicone adhesive film by crosslinking at a temperature in the C range. Claim 19 A method for manufacturing a silicone adhesive film according to claim 15, wherein the step of providing the methylphenyl group-containing polysiloxane comprises: a step of forming a first mixture by stirring a siloxane oligomer and a retardant; a step of forming a second mixture by stirring the first mixture and the methylphenyl siloxane; a step of forming a third mixture by stirring the second mixture and a platinum catalyst; and a step of polymerizing the siloxane oligomer and the methylphenyl siloxane by heating the third mixture. Claim 20 A method for manufacturing a silicone adhesive film according to claim 19, wherein, after performing the polymerization step, methylphenylsiloxane is added to the polymerized polysiloxane formed to form a polysiloxane having a desired molecular weight, and the polymerization reaction is repeated.
Citation Information
Patent Citations
Dual-curing adhesive composition and method for preparing and using the same
KR1020200043411A
Adhesive film with interpenetration polymer network, method for fabricating the same and foldable display device including the same
KR1020250046433A
Heat-curable siloxane encapsulant components
KR1020130068021A
Silicone pressure-sensitive adhesive composition
KR1020200035474A
Use of aryl-containing organopolysiloxane gums as additives to improve rheological behavior
KR1020220167327A
